Legal Protection for Domestic Violence Due to Advances in Information and Communication Technology - Lasmin Alfies Sihombing (Faculty of Law, Universitas Pekalongan, 2021)
In the ever-evolving digital era, technological developments have had a significant impact on social relationships and family dynamics. Although ICT offers various conveniences in communicating and accessing information, there are challenges and risks associated with using this technology. This study seeks to examine the impact of advances in information and communication technology (ICT) on intimate partner violence (KDRT) and the penal law protections available in this context. This study employs a normative legal research methodology to investigate and analyze legal materials and related literature on domestic violence and the impact of ICT developments. According to the findings of this study, the development of information and communication technology (ICT) has had a significant effect on the incidence of domestic violence (KDRT). Online Gender-Based Violence (KBGO) has emerged as a new form of violence that employs technology to harass, denigrate, exploit, and intimidate victims on the basis of their gender or sexuality. Domestic violence perpetrators use Law no. 11 of 2008 concerning Information and Electronic Transactions (ITE) in Indonesia, specifically Article 27 Paragraphs (1) and (3) Jo. Article 45 of the ITE Law, to suppress domestic violence victims and continue the misuse of technology. However, the existence of the ITE Law in the context of KBGO has also raised concerns regarding free speech and the protection of domestic violence victims..